Introduction to the Special Feature: Will the BRIC Decade Continue? The Role of Rural Areas and Agriculture - Stephan Brosig; Ramona Teuber; Inna Levkovych; Rainer Thiele; Thomas Glauben (Journal of Agricultural Economics, 2013)
This article provides an introduction to the special feature on agriculture-related issues in the emerging economies of Brazil, Russia, India and China (BRIC) contained in this issue of Journal of Agricultural Economics. The special feature is motivated by the increased interest which these countries have received since the turn of the millennium and by the significance of agriculture in their development. It considers economic and social development in BRICs, their integration in world agricultural trade as well as environmental concerns. This article presents key figures on economic, social and agricultural features in BRICs and compares them across countries. A synthesis of the articles included in the special feature is provided by highlighting the selection of topics likely to be crucial for further development across BRICs.
Keywords: F63; Q17; Q56; I32; 330; BRIC; agricultural trade; agricultural sector